2016
DOI: 10.1177/0271678x16661202
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic clearance controls state-dependent changes in brain lactate concentration

Abstract: Brain lactate concentration is higher during wakefulness than in sleep. However, it is unknown why arousal is linked to an increase in brain lactate and why lactate declines within minutes of sleep. Here, we show that the glymphatic system is responsible for state-dependent changes in brain lactate concentration. Suppression of glymphatic function via acetazolamide treatment, cisterna magna puncture, aquaporin 4 deletion, or changes in body position reduced the decline in brain lactate normally observed when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
214
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(242 citation statements)
references
References 77 publications
(154 reference statements)
13
214
0
2
Order By: Relevance
“…Bosoi et al suggested that increased lactate contributes to the pathogenesis of brain edema (cytotoxic) and may imply that the observed increase in total brain lactate is due to its intracellular accumulation. If the rate of lactate production and glymphatic clearance (38) are not affected, intracellular retention of lactate would explain higher concentration of this metabolite as measured by NMR spectroscopy (39) and would be in full agreement with our data showing impairment of hemichannel-mediated release in HE.…”
Section: Discussionsupporting
confidence: 90%
“…Bosoi et al suggested that increased lactate contributes to the pathogenesis of brain edema (cytotoxic) and may imply that the observed increase in total brain lactate is due to its intracellular accumulation. If the rate of lactate production and glymphatic clearance (38) are not affected, intracellular retention of lactate would explain higher concentration of this metabolite as measured by NMR spectroscopy (39) and would be in full agreement with our data showing impairment of hemichannel-mediated release in HE.…”
Section: Discussionsupporting
confidence: 90%
“…Tissue samples of MTS have been shown to present a striking lack of peri‐vascular AQP4 water channels that mediates the glymphatic water clearance (Eid et al., 2005). The absence of AQP4 channels in MTS areas could lead to altered extracellular electrolyte concentrations that sensitizes neuronal tissue to seizures (Eid et al., 2005; Lundgaard et al., 2017; Marchi et al., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…knockout, CSF volume reduction, or alteration of posture all led to increased brain and reduced cervical lymph node lactate levels (21), even in the clearance-promoting anesthetized state (20). The importance of glymphatic clearance of interstitial solute is perhaps best demonstrated by the fact that its failure contributes to the pathophysiology of various CNS diseases.…”
Section: The Glymphatic System: Anatomy and Function In Health And DImentioning
confidence: 99%